2008
DOI: 10.1097/sap.0b013e3181579900
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Microvascular Protocols for Lower Extremity Free Tissue Transfer II

Abstract: Due to the complex, and often tenuous nature of microsurgical tissue transfer, postoperative monitoring of free tissue flaps plays a vital role in the management of such patients. Some of the more challenging reconstructive problems occur in patients with lower extremity trauma, yet to date, no preferred protocol exists for the postoperative care of lower extremity free flaps. The present study sought to evaluate and assess current preferences in monitoring following lower extremity free tissue transfer. Membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 9 publications
1
55
0
Order By: Relevance
“…Temperature, skin color, capillary refill, active bleeding, tissue turgor, and the use of the handheld Doppler probe are all useful for monitoring flaps. 3,4 These techniques are simple to use, inexpensive, non-invasive and reproducible. However these techniques require interpretation by experienced staff, and require the same staff member to repeat the examination in order to avoid interobserver variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature, skin color, capillary refill, active bleeding, tissue turgor, and the use of the handheld Doppler probe are all useful for monitoring flaps. 3,4 These techniques are simple to use, inexpensive, non-invasive and reproducible. However these techniques require interpretation by experienced staff, and require the same staff member to repeat the examination in order to avoid interobserver variability.…”
Section: Discussionmentioning
confidence: 99%
“…The Doppler probe has also been used as an adjunct to clinical monitoring, 3,4 with Doppler shown to be noninvasive, inexpensive, easy to perform, and reproducible. 5,6 However, limitations to these techniques include a degree of inaccuracy due to the subtle nature of the signs of vascular compromise, the inability to perform continuous monitoring, and the need for flap exposure to perform the tests.…”
mentioning
confidence: 99%
“…160 Survey data of active microsurgeons showed that 43 percent dangle at 2 to 5 days, 38 percent dangle at 6 to 13 days, and the duration of the dangling varies widely. 161 A recent prospective, randomized, controlled clinical trial of 31 trauma patients showed that an early and aggressive start of a combined dangling/wrapping at day 3 did not compromise flap circulation or overall outcome (Level II Evidence). 162 Our dangling protocol is listed (Table 4).…”
Section: Dangling Protocolsmentioning
confidence: 98%
“…However, these protocols differ greatly, especially considering the timing of first dependency and duration of training. 6 Although lower extremity reconstruction and dangling procedures are an essential part of day-to-day practice at a reconstructive center, there is little evidence considering the microcirculatory changes in lower extremity free flaps during dangling. The published studies are either solely based on clinical examination or include only a very limited number of patients.…”
mentioning
confidence: 99%
“…Although there are recommendations for postoperative care, a recent survey shows great diversity considering this topic. 5,6 Especially in lower extremity reconstruction, there is a need for a structured training of the flap. The gravitational challenge associated with dependency of the lower extremity can cause Keywords ► microsurgery ► dangling ► free flap ► lower extremity reconstruction Abstract Lower extremity reconstruction utilizing free tissue transfer has become a common and safe procedure.…”
mentioning
confidence: 99%